60 years since the “Seven thesis”: Rodolfo Stavenhagen’s critical trajectory: 60 anos das “Siete tesis”: a trajetória crítica de Rodolfo Stavenhagen (Revista de História da UEG (REVHIST), 2024)
2025 will mark the 60th anniversary of “Siete thesis equivocadas sobre América Latina”, by Mexican anthropologist and sociologist Rodolfo Stavenhagen. At the time of its publication, this article had a wide repercussion on a range of debates: from criticism of CEPAL’s dualism to critics toward indigenistas policies. Born in Frankfurt in 1932 and coming from a Jewish family, Stavenhagen arrived in Mexico at the age of eight, fleeing Nazi persecution. Until his death in 2016, he worked as an intellectual committed to social critic and transformation, especially in favor of the rights of indigenous peoples. Since his master's degree at ENAH University in the 1950s, Stavenhagen developed criticisms of the indigenista paradigm of incorporating indigenous people into the Mexican nation, positioning himself as a leading figure in the new generation of radical Mexican anthropologists that would emerge in the following decades. His concept of “internal colonialism”, formulated in the 1960s together with his colleague Pablo González Casanova, became an indispensable tool for the analysis of interethnic relations in Latin America. In this article, I intend to present the historical evolution of this author is thinking and his main contributions to Latin American social theory.Keywords: Indigenismo, dualism, indigenous peoples, internal colonialism, human rights.